ANALYSIS OF THE CHARACTERISTICS OF CHILDREN WITH AUTISM AND HOW TO LEARN USING AUDIO-VISUAL MEDIA - Susanti, Amalia (JPI (Jurnal Pendidikan Inklusi), 2024)
Autism is an overall developmental disorder that causes problems with behavior, abilities, socialization, and communication. Autistic children have very complex problems that require special attention to help them interact well. This research examines the characteristics of children with special needs in autistic children and how to learn using audio-visual media. The research method used is a qualitative method. The results of research using audio-visual media can be used for learning for autistic children. With audiovisual media, autistic children can communicate through movements that have been broadcast via audiovisual media. This can train communication in autistic children.